Metode Praktis Dalam Estimasi Respons Dinamik Tanah Akibat Gempa Dan Stabilitas Timbunan Berlereng Di Atas Situs Tanah Sedang - Sofyan, Delfebriyadi (Universitas Andalas, 2025)
The use of practical methods in calculating the dynamic response of soil due to the propagation of earthquake waves in soil deposits and their impact on the structure above it is presented in this paper. Practical methods are commonly used in preliminary design to estimate the ideal structural dimensions from the available data obtained from field and laboratory investigations before being further processed in detail with engineering programming tools. In this paper, calculations are carried out referring to tables published in SNI-1726 and reference paper tables. A case study was conducted on a sloped embankment against seismic loads on a medium soil class (Sd) site. The results obtained are a mapping of the slope safety factor due to selected earthquake accelerations that are applied to the structure.